Trial Watch: Immunostimulation with Toll-like receptor agonists in cancer therapy - Iribarren, Kristina; Bloy, Norma; Buqué, Aitziber; Cremer, Isabelle; Eggermont, Alexander; Fridman, Wolf Hervé; Fucikova, Jitka; Galon, Jérôme; Špíšek, Radek; Zitvogel, Laurence; Kroemer, Guido; Galluzzi, Lorenzo (Oncoimmunology, 2016)
Accumulating preclinical evidence indicates that Toll-like receptor (TLR) agonists efficiently boost tumor-targeting immune responses (re)initiated by most, if not all, paradigms of anticancer immunotherapy. Moreover, TLR agonists have been successfully employed to ameliorate the efficacy of various chemotherapeutics and targeted anticancer agents, at least in rodent tumor models. So far, only three TLR agonists have been approved by regulatory agencies for use in cancer patients. Moreover, over the past decade, the interest of scientists and clinicians in these immunostimulatory agents has been fluctuating. Here, we summarize recent advances in the preclinical and clinical development of TLR agonists for cancer therapy.
Keywords: motolimod; G100; Ampligen™; Hiltonol™; imiquimod; bacillus Calmette-Guérin